Phase Shift Full Bridge DC–DC Converter With Active Clamping Circuit for Fuel Cell Electric Vehicles - Bader N. Alajmi; Nabil A. Ahmed; Ibrahim Abdelsalam; Mostafa I. Marei (IEEE Access)
This paper proposes a soft switching isolated phase-shifted full-bridge DC-DC converter using active clamping circuit for fuel cell power generation applications. An active clamping circuit is added to the primary side of the high frequency transformer to clamp voltage spikes and recycle the energy trapped in the leakage inductor. The presented converter has the advantages of a small number of components, simple circuit configuration, reduced voltage stress and a wide input voltage range. The soft switching operation of the presented converter allows for high switching frequency with high power conversion efficiency. Analysis, simulation, operation principles and a design example of the proposed converter are conducted using PSIM simulation software. Various operation modes and their equivalent circuits during each operating cycle are investigated in detail. A down scale 1.2 kW of simulation and 350 W of experimental prototypes are developed to validate the wide output voltage gain of the proposed converter employing a wide range low input voltage to maintain a regular output voltage with a maximum power conversion efficiency of 98% and 96.5% at full load are achieved due to the ability of the proposed converter to minimize switching losses rated power conditions. The results from simulation and experimentation are used to validate the operation and modeling and to strengthen the viability and efficiency of the suggested converter topology.